The Cambridge companion to twentieth-century British and Irish women's poetry - Dowson, Jane (Cambridge University Press, 2011)
"This Companion provides new ways of reading a wide range of influential women's poetry. Leading international scholars offer insights on a century of writers, drawing out the special function of poetry and the poets' use of language, whether it is concerned with the relationship between verbal and visual art, experimental poetics, war, landscape, history, cultural identity or 'confessional' lyrics. Collectively, the chapters cover well established and less familiar poets, from Edith Sitwell and Mina Loy, through Stevie Smith, Sylvia Plath and Elizabeth Jennings to Anne Stevenson, Eavan Boland and Jo Shapcott. They also include poets at the forefront of poetry trends, such as Liz Lochhead, Jackie Kay, Patience Agbabi, Caroline Bergvall, Medbh McGuckian and Carol Ann Duffy. With a chronology and guide to further reading, this book is aimed at students and poetry enthusiasts wanting to deepen their knowledge of some of the finest modern poets"--